Virological and Clinical Studies of Viral Hemorrhagic Fever (VHF): A Systematic Literature Review - Fadrian; Armen Ahmad; Zaki Mahmudi Dasril (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Viral hemorrhagic fever (VHF) is a group of zoonotic diseases caused by various RNA viruses, such as Ebola, Marburg, Lassa, Crimean-Congo hemorrhagic fever (CCHF), and Dengue. VHF poses a serious threat to global public health due to high morbidity and mortality rates. This study aims to conduct a systematic literature review of virological and clinical studies of VHF to understand the characteristics of the virus, pathogenesis, clinical manifestations, risk factors, diagnosis, and current therapeutic options. Methods: A comprehensive literature search was conducted on PubMed, Scopus, and Web of Science databases to identify relevant studies published between 2018 and 2024. Studies that met the inclusion criteria were evaluated for quality and narratively synthesized. Results: This review included 20 studies involving 2,350 VHF patients. Results demonstrated significant diversity in virologic characteristics, pathogenesis, and clinical manifestations among different types of VHF. These studies also highlight advances in molecular and serological diagnosis, as well as the development of antiviral and immunomodulatory therapies. Conclusion: This systematic literature review provides a comprehensive summary of current knowledge regarding the virology and clinical practice of VHF. These findings may guide the development of more effective prevention, diagnosis, and treatment strategies for this life-threatening disease.